2014
DOI: 10.2139/ssrn.2490044
|View full text |Cite
|
Sign up to set email alerts
|

Primaries and Candidates: Examining the Influence of Primary Electorates on Candidate Ideology

Abstract: Primary elections in the United States have been under-studied in the political science literature. Using new data to estimate the ideal points of primary election candidates and constituents, we examine the link between the ideological leanings of primary electorates and the ideological orientation of U.S. congressional candidates. We use district-level data from the Cooperative Congressional Election Study and ideal point estimates for congressional primary election candidates to examine the role of primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Furthermore, candidates of both parties tend to be more ideologically extreme than general election voters. For a discussion, see Nielson and Visalvanich ().…”
mentioning
confidence: 99%
“…Furthermore, candidates of both parties tend to be more ideologically extreme than general election voters. For a discussion, see Nielson and Visalvanich ().…”
mentioning
confidence: 99%
“…Our results rely on the fact that parties can choose any available platform location. However, parties may nominate extreme candidates who will be unwilling to choose moderate policies (Hall 2019;Nielson and Visalvanich 2017). consider a situation where L could only choose a platform more extreme than some cutoff platform κ l .…”
Section: Empirical Discussionmentioning
confidence: 99%
“…This is true, but the issue is whether party leaders are themselves selected through a primary election mechanism. 9Nielson and Visalvanich (2017), using data from USA congressional candidates, found that ideology does play a role and voters are responsive to different candidates. As a matter of fact, they found that extreme Republicans have a greater chance to win a primary and be selected as a party nominee.…”
mentioning
confidence: 99%